William Golding - Dick, Bernard F. (Boston : Twayne, 1987)
Bibliography: p. 162-165. A critical survey of Golding's entire body of work including his novels, poems, and nonfiction.
Includes index.
Bibliography: p. 162-165.
Wilson's Public Library.
Young Adult.
Young Adult
Keywords: Golding, William, -- 1911- -- Criticism and interpretation; Golding, William, -- 1911-